2005
DOI: 10.1038/sj.ejhg.5201369
|View full text |Cite
|
Sign up to set email alerts
|

A 2.3 Mb duplication of chromosome 8q24.3 associated with severe mental retardation and epilepsy detected by standard karyotype

Abstract: Chromosome duplications are found in about 2% of subjects with a typical chromosomal phenotype but their frequency is likely to be higher, as suggested by the first array-CGH data. According to the orientation of the duplicated segment, duplications may be in tandem or inverted. The latter are usually associated with a distal deletion. We studied a de novo 2.3 Mb inverted duplication of 8q24.3 without apparently associated deletion in a subject with profound psychomotor retardation, idiopathic epilepsy and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
(22 reference statements)
2
36
0
Order By: Relevance
“…Many other examples of inverted duplication deletions have now been reported, suggesting that the mechanism responsible for the inv dup(8p) can be generalized to all inverted duplications [Bonaglia et al, 2000;Ciccone et al, 2006]. However, Bonaglia et al [2005] could not demonstrate, nor exclude, in an atypical inv dup(8q) without apparently associated deletion, the presence of the distal deletion associated to the duplication, as in the 8q24.3 region, two genome sequence gaps are still present. In our rearrangement, a single-copy region between the deleted and duplicated regions, usually described in the inv dup del chromosomes, was not detected.…”
Section: Discussionmentioning
confidence: 98%
“…Many other examples of inverted duplication deletions have now been reported, suggesting that the mechanism responsible for the inv dup(8p) can be generalized to all inverted duplications [Bonaglia et al, 2000;Ciccone et al, 2006]. However, Bonaglia et al [2005] could not demonstrate, nor exclude, in an atypical inv dup(8q) without apparently associated deletion, the presence of the distal deletion associated to the duplication, as in the 8q24.3 region, two genome sequence gaps are still present. In our rearrangement, a single-copy region between the deleted and duplicated regions, usually described in the inv dup del chromosomes, was not detected.…”
Section: Discussionmentioning
confidence: 98%
“…34 Interestingly, human TMBIM3 gene location maps close to a locus genetically linked with epilepsy. 35 A viable tmbim3 knock-out mice was recently generated confirming the neuronal expression of TMBIM3 in mice. 36 However, no functional analysis of TMBIM3 KO mice was performed.…”
mentioning
confidence: 97%
“…Deletions/duplications of 8q24 have been rarely reported in the literature and, to the best of our knowledge, only four papers have described this chromosome rearrangement (Eussen et al, 2000;Bonaglia et al, 2005;Gradek et al, 2006;Tokutomi et al, 2007) in patients with phenotypes different from that of our case. Bonaglia et al (2005) and Eussen et al (2000) both described a duplication of chromosome 8q24.3: the former associated with epilepsy and severe mental retardation and the latter with tuberous sclerosis complex, adult polycystic kidney disease, and hypomelanosis of Ito.…”
Section: Discussionmentioning
confidence: 51%
“…Bonaglia et al (2005) and Eussen et al (2000) both described a duplication of chromosome 8q24.3: the former associated with epilepsy and severe mental retardation and the latter with tuberous sclerosis complex, adult polycystic kidney disease, and hypomelanosis of Ito. On the other hand, Gradek et al (2006) and Tokutomi et al (2007) reported a deletion of the region 8q24.3 K qter: the first present in a mosaic patient with mild phenotype and the second in a girl with hepatic focal nodular hyperplasia.…”
Section: Discussionmentioning
confidence: 99%